Presidential Decree-Law No. 103 of the Year 2015 Amending Certain Provisions of Law No. 48 of the Year 1982 Regarding the Protection of the River Nile and Waterways From Pollution = قرار رئيس جمهورية مصر العربية بالقانون رقم 103 لسنة 2015 بتعديل بعض أحكام القانون رقم 48 لسنة 1982 فى شأن حماية نهر النيل والمجارى المائية من التلوث - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic